Solugas – Comprehensive analysis of the solar hybrid Brayton plant. (October 2016) - Korzynietz, R.; Brioso, J.A.; del Río, A.; Quero, M.; Gallas, M.; Uhlig, R.; Ebert, M.; Buck, R.; Teraji, D.
Highlights: Demonstration of the feasibility of a solar-hybrid plant with gas turbine. Solugas plant operation data and behaviour. Pressurised tubular air receiver efficiency evaluation. Great performance of heat exchange process achieving receiver outlet temp of 800 °C. Abstract: This article presents the first megawatt scale solar-hybrid plant with a solarized gas turbine. The works and improvements that made the Solugas project succeed during design, construction and long-term solar operation are described and explained. More than 1000 operation hours and receiver outlet temperatures of 800 °C were achieved. The operation behaviour and performance of the key components – the solar pressurised air receiver and the gas turbine – are presented here as a proof of the high potential of the technology.